Hail Chicago! - Bob Allan::::::::: (Leo Feist Inc.)
Piano and vocal score, 5 p. At head of title on cover: Official song of the pageant of progress. Also on cover: The $2,000 prize winner in the Chicago Herald-Examiner song contest. Composers name on cover shown as Bob Allen. Publishers advertisement on verso of last leaf.